Role of Mirena in Dub Patients (Journal of Chittagong Medical College Teachers' Association, 2014)
To determine the effectiveness of Mirena in achieving a reduction in heavy menstrual blood loss in dysfunctional uterine bleeding. To evaluate improvement in Haemoglobin level (Hb gm%) in patients during treatment period. The study was conducted in the department of Obstetrics & Gynaecology, Chittagong Medical College Hospital, Chittagong, Bangladesh from August 2008 to July 2010. Thirty six patients with Dysfunctional Uterine Bleeding (DUB) in 30-45 years age group with Body Mass Index (BMI) of 18-30 during treatment period were included in this study. They were counseled, investigated and Levonogestrel Intrauterine device Mirena was inserted. Outcome was measured by the Hb improvement and decrease in blood loss both in amount and duration. Record was kept and follow up was done. Ninety percent of the patients were relived from menorrhagia and one hundred percent improvement was seen in cases with polymenorrhagia. Fifty percent patients had an Hb of >11.1 gm% after 3 months of use. Mirena is a safe and effective device for treatment of DUB patients and it is an alternative to hysterectomy.JCMCTA 2014 ; 25 (1): 8-11